To find the x-intercepts of the function \( G(x) = (4x - 1)(x + 2) \), we need to set \( G(x) \) equal to zero and solve for x:
\[ (4x - 1)(x + 2) = 0 \]
This equation will be true when either factor is zero:
-
Set \( 4x - 1 = 0 \): \[ 4x = 1 \implies x = \frac{1}{4} \]
-
Set \( x + 2 = 0 \): \[ x = -2 \]
Thus, the x-intercepts are \( \left(\frac{1}{4}, 0\right) \) and \( (-2, 0) \).
Now, examining the answer choices:
A. \( (1,0) \) and \( (2,0) \) - Incorrect B. \( (0,25, 0) \) and \( (-2,0) \) - Incorrect C. \( (-0,25, 0) \) and \( (2,0) \) - Incorrect D. \( (-1,0) \) and \( (2,0) \) - Incorrect
None of the options provided are correct. The correct x-intercepts are \( \left(\frac{1}{4}, 0\right) \) and \( (-2, 0) \).